Performance Prediction of Plate-Finned Tube Heat Exchangers for Refrigeration: A Review on Modeling and Optimization Methods - Silvia Macchitella; Gianpiero Colangelo; Giuseppe Starace (Energies, 2023)
Finned tube heat exchangers are used in many technological applications in both civil and industrial sectors. Their large-scale use requires a design aimed at reaching high thermal efficiency as well as avoiding unnecessary waste of resources in terms of time and costs. Therefore, in the last decades, research in this area has developed considerably and numerous studies have been conducted on modeling in order to predict heat exchangers (HXs) performance and to optimize design parameters. In this paper, the main studies carried out on plate-finned tube HXs have been collected, analyzed, and summarized, classifying existing models by their scale approach (small, large, or multi-scale). In addition, the main methods of design optimization with a focus on circuitry configurations have been illustrated. Finally, future developments and research areas that need more in-depth analysis have been identified and discussed.